Layanan Dan Informasi Akademik Berbasis Bot Telegram Di Program Studi Teknik Informatika Universitas Mataram - Ariyan Zubaidi; Ramdani Ramdani (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
Chatbot is considered as one of the hottest technology in recent years. It is used by various sector to serve its customer automatically. It gives benefits to business, primarily in customer care. Chatbot can be divided into 2 (two) types. One operates based on set of rules. It can be used with set of spesific command. The other types uses machine learning and artificial intelligence to provide its service. Chatbot can be utilised as well in education sector. Campus gives service to its students or faculty by providing information and academic service. Commonly, academic information and service has supported by information technology, usually in particular website. But, not all of the services are available and newest information does not always accessed timely. Hence, this research built a chatbot based on Telegram to provide information and academic services in informatic engineering department of mataram university. Telegram provides API that can be used to develop bot. The bot is built using Python, SQLite as the database and React. Prototyping model is used as a development method. The bot prototype is able to broadcast newest information to its register user and provides academic service such as theses program and internship program.